Effect of silver electrode wetting state on oxygen reduction electrochemistry. Issue 65 (30th June 2021) - McKee, Austin; Samanta, Avik; Rassoolkhani, Alan; Koonce, Jonathan; Huang, Wuji; Fields, Jacob; Shaw, Scott K.; Gomes, Joseph; Ding, Hongtao; Mubeen, Syed
Abstract : Direct tuning of silver electrode wetting state affects its activity and selectivity for oxygen reduction reaction. Abstract : Surface wettability plays an important role in heterogeneous electrocatalysis. Here we report a facile laser ablation strategy to directly modify the wettability of the silver catalyst surface and investigate its effect on oxygen reduction reaction (ORR). A broad range tuning of 2e − /4e − ORR pathways was achieved, with hydrophilic silver surfaces (contact angle ( θ w ) 31.1° ± 0.6°) showing high activity and selectivity towards 4e − reduction of oxygen to water.